Fluency with information technology : - Snyder, Lawrence (Pearson Addison Wesley, 2004)
Fluency with Information Technology gives students the experience, knowledge, and capabilities needed to apply information technology effectively throughout their lives. Unlike computer literacy, which teaches only immediately useful skills, Fluency with Information Technology adds problem solving, reasoning and complexity management to prepare students to use computers today and to be effective technology users tomorrow